2022
DOI: 10.21608/edj.2021.109385.1889
|View full text |Cite
|
Sign up to set email alerts
|

Estimation of Vitamin D Gingival Crevicular Fluid Level In Patients With Different Periodontal Conditions.

Abstract: Background: Vitamin D (Vit. D) is responsible in the process of calcium homeostasis, among many other biological effects. Thus it plays an essential role in bone related diseases. Furthermore, several studies investigated the link between Vit. D plasma level and various conditions of periodontal diseases.Objective: Therefore, the present study aimed to assess Vit. D3 [25(OH) D] gingival crevicular fluid (GCF) levels in individuals with different periodontal conditions.Subjects and methods: 60 GCF samples were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 34 publications
0
4
1
Order By: Relevance
“…Banna SE et al also confirmed the relationship between the severity and progression of periodontal disease with visfatin levels. In their study, visfatin level was higher in chronic periodontitis and gingivitis than in healthy subjects, but the difference between the chronic periodontitis group and gingivitis group was not statistically significant [25] as we did. Turer CC et al [43] also supposed that the level of visfatin in patients with gingivitis was higher than in healthy patients, and chronic periodontitis was higher than in both cases and in fact, the concentration of visfatin was proportional to the severity of the inflammation of the disease.…”
Section: Plos Onecontrasting
confidence: 67%
See 4 more Smart Citations
“…Banna SE et al also confirmed the relationship between the severity and progression of periodontal disease with visfatin levels. In their study, visfatin level was higher in chronic periodontitis and gingivitis than in healthy subjects, but the difference between the chronic periodontitis group and gingivitis group was not statistically significant [25] as we did. Turer CC et al [43] also supposed that the level of visfatin in patients with gingivitis was higher than in healthy patients, and chronic periodontitis was higher than in both cases and in fact, the concentration of visfatin was proportional to the severity of the inflammation of the disease.…”
Section: Plos Onecontrasting
confidence: 67%
“…Only in two studies [ 16 , 25 ], visfatin levels in GCF were compared between gingivitis patients and healthy individuals, and 20 healthy cases and 30 gingivitis patients were included in the analysis, and SMD was estimated as 2.60 ng/ml (95% confidence interval (CI): -0.40–5.62, p = 0.090) ( Table 2 ). The results of the present study showed that the visfatin level in the GCF of gingivitis patients and healthy individuals are the same.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations